2018
DOI: 10.1016/j.celrep.2017.12.085
|View full text |Cite
|
Sign up to set email alerts
|

Mannose Receptor 1 Restricts HIV Particle Release from Infected Macrophages

Abstract: SUMMARY Human mannose receptor 1 (hMRC1) is expressed on the surface of most tissue macrophages, dendritic cells, and select lymphatic or liver endothelial cells. HMRC1 contributes to the binding of HIV-1 to monocyte-derived macrophages (MDMs) and is involved in the endocytic uptake of HIV-1 into these cells. Here, we identify hMRC1 as an antiviral factor that inhibits virus release through a bone marrow stromal antigen 2 (BST-2)-like mechanism. Virions produced in the presence of hMRC1 accumulated in clusters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 46 publications
6
31
0
Order By: Relevance
“…As recently reported by Sukegawa at al. (2018) with reference to HIV-1, MRC1 inhibits virus release and mediates HIV retention on the surface of virus-producing cells, thus causing a reduction in the progression of infection [ 53 ]. To the best of our knowledge, the possible involvement of MRC1 in the HCMV replication cycle has never been investigated.…”
Section: Resultsmentioning
confidence: 99%
“…As recently reported by Sukegawa at al. (2018) with reference to HIV-1, MRC1 inhibits virus release and mediates HIV retention on the surface of virus-producing cells, thus causing a reduction in the progression of infection [ 53 ]. To the best of our knowledge, the possible involvement of MRC1 in the HCMV replication cycle has never been investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we could not exclude the hypothesis that Vpu interferes with another cellular partner to regulate the VCCs' size. Interestingly, several additional factors, such as Siglec-1 and mannose receptor 1, have been described to tether virus and favor their sequestration in MDMs (17,63). Moreover, several studies report that Vpu downregulates the tetraspanins CD63, CD81, and CD82 that are found enriched in VCCs (64)(65)(66).…”
Section: Discussionmentioning
confidence: 99%
“…Klaus Strebel (National Institute of Allergy and Infectious Diseases, NIH) described his work on the role of human mannose receptor (hMRC1) in antagonizing lentiviral replication [ 51 ]. This factor functions in macrophages to inhibit the detachment of budded virions from the cell surface in a manner much like tetherin.…”
Section: Env Trafficking and Incorporationmentioning
confidence: 99%
“…This factor functions in macrophages to inhibit the detachment of budded virions from the cell surface in a manner much like tetherin. Strebel’s group showed that the HIV-1 AD8 strain counteracts the effect of hMRC1 by reducing its expression via transcriptional silencing [ 51 ]. hMRC1 directly binds all of the HIV-1 Env isolates tested, but the connection between Env and hMRC1 binding remains unclear, as the release of VLPs not bearing HIV-1 Env glycoproteins is still inhibited by hMRC1 [ 51 ].…”
Section: Env Trafficking and Incorporationmentioning
confidence: 99%
See 1 more Smart Citation